An assessment of the impact of customers and suppliers as competitive forces in Polish car communication enterprises - Budzik, Tomasz; Budzik, Anna (Ocena oddziaływania klientów i dostawców jako sił konkurencyjnych w przedsiębiorstwach komunikacji samochodowej, 2019)
The aim of the article is to assess the impact of recipients and suppliers on the state-owned PKS enterprises. A non-random choice was used to select a research sample. The choice was deliberate with the use of the appropriate criteria. The enterprises forming the strategic group and at the same time being the research group were selected. The qualitative methods were used in the research. The article uses Porter’s Five Forces Framework tool. On the basis of the partial analysis of Porter’s Five Forces, it is stated that the surveyed enterprises have a stronger influence on the suppliers than on the customers. The functioning of the surveyed group of enterprises is significantly dependent on suppliers. In turn, the customers of the examined group of enterprises affect its functioning to a small extent. The article aims to fill the research gap existing in the lack of in-depth research in the field of strategic analysis on these enterprises. The presented research can be used to create an individual strategy and achieve a competitive advantage of each company in the strategic group
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 203-216
Keywords: regional transport; car communication enterprises; PKS; environmental analysis; Porter's five forces; transport regionalny; przedsiębiorstwa komunikacji samochodowej; analiza otoczenia; pięć sił Portera